Phase-Shift Keying Modulated Data Signal Using SOA-MZI-Based All-Optical Logic AND Gate at 80 Gb/s - Amer Kotb; Yasser Mohamed (International Journal of Optics)
All-optical logic AND operation with phase-shift keying (PSK) modulated data signals based on a semiconductor optical amplifier (SOA) assisted Mach-Zehnder interferometer is numerically analyzed and investigated. By solving the rate equations of the SOA, the dependence of the quality factor on the critical parameters of the input signal and the SOA is examined, including the impact of the amplified spontaneous emission to obtain realistic results. The obtained results confirm that the all-optical logic AND scheme with PSK modulated data signals is capable of operating at a data rate of 80 Gb/s with both logical correctness and acceptable quality compared to the system using on-off-keying signal.